Pseudoalteromonas flavipulchra as a dual-functional probiotic for aquaculture: enhancing microalgae growth and antagonizing Vibrio pathogens - Wu, Min-nan; Xu, Yi-jun; Shao, Meng-meng; Wang, Zi-yue; Cao, Jia-yi; Xu, Ji-lin (Frontiers in Marine Science, 2024)
Vibrio disease is a prevalent bacterial infection in aquaculture, and using bacteria with antagonistic properties against Vibrio species as probiotics has emerged as a promising method for disease prevention. Additionally, low biomass productivity of microalgae feed remains a significant bottleneck in bivalve aquaculture. Therefore, it is essential to screen for bacteria that both enhance microalgae growth and inhibit Vibrio pathogens. In this study, seven bacterial strains capable of promoting microalgae growth were screened for their ability to inhibit three Vibrio pathogens, i.e., Vibrio vulnificus, Vibrio parahaemolyticus and Vibrio cholerae, and thus serve as a dual-functional probiotic for aquaculture. The antagonistic mechanism of these bacteria was further investigated by analyzing the inhibitory effects of their extracellular products (ECP) on Vibrio species. Results indicated that Pseudoalteromonas flavipulchra exhibited antagonistic effects against all three Vibrio species tested. The ECP of P. flavipulchra displayed stable antibacterial activity, though this ability was lost after the ECP was treated with heat, alkali, or proteinase K. The proteinaceous fraction isolated from the ECP by precipitation with 90% saturated ammonium sulfate demonstrated concentration-dependent antibacterial activity. These findings suggest that P. flavipulchra could serve as a promising dual-functional probiotic for aquaculture, warranting further research to optimize its application in this field.